The impact of international mobility as experienced by Spanish academics. Issue 1 (2nd January 2018) - Groves, Tamar; López, Estrella Montes; Carvalho, Teresa
ABSTRACT: The objective of this research is to explore the experiences of the first generations of Spanish academics that carried out research stays in foreign institutions. The analysis of 30 semi-structured interviews shows the interviewees' evaluation of their stay abroad, the impact that this had on their academic career and how the return to the home institution was a complex process of adaptation. It is an exploratory research which attempts to contribute to current debates about international mobility of academic staff. While it confirms that generally speaking mobility is perceived as positive there are negative aspects related to academics' (re)integration related to cultural specificities and of the maturity of the scientific system.